Annual Book of ASTM Standards 2006 : Section XV : General Products, Chemical Specialties and End Use Products, Vol. 15.03 : Space Simulation, Aerospace & Aircraft, Composite Materials - ASTM (2006)
Koleksi Referensi (Tidak Dipinjamkan)